Evaluation and Management of Premature Ventricular Complexes. Issue 17 (28th April 2020) - Marcus, Gregory M.
Abstract : Premature ventricular complexes (PVCs) are extremely common, found in the majority of individuals undergoing long-term ambulatory monitoring. Increasing age, a taller height, a higher blood pressure, a history of heart disease, performance of less physical activity, and smoking each predict a greater PVC frequency. Although the fundamental causes of PVCs remain largely unknown, potential mechanisms for any given PVC include triggered activity, automaticity, and reentry. PVCs are commonly asymptomatic but can also result in palpitations, dyspnea, presyncope, and fatigue. The history, physical examination, and 12-lead ECG are each critical to the diagnosis and evaluation of a PVC. An echocardiogram is indicated in the presence of symptoms or particularly frequent PVCs, and cardiac magnetic resonance imaging is helpful when the evaluation suggests the presence of associated structural heart disease. Ambulatory monitoring is required to assess PVC frequency. The prognosis of those with PVCs is variable, with ongoing uncertainty regarding the most informative predictors of adverse outcomes. An increased PVC frequency may be a risk factor for heart failure and death, and the resolution of systolic dysfunction after successful catheter ablation of PVCs demonstrates that a causal relationship can be present. Patients with no or mild symptoms, a low PVC burden, and normal ventricular function may be best served with simple reassurance. Either medical treatment or catheter ablation are considered first-line therapies in most patients with PVCs associated with symptoms or a reduced left ventricular ejection fraction, and patient preference plays a role in determining which to try first. If medical treatment is selected, either β-blockers or nondihydropyridine calcium channel blockers are reasonable drugs in patients with normal ventricular systolic function. Other antiarrhythmic drugs should be considered if those initial drugs fail and ablation has been declined, has been unsuccessful, or has been deemed inappropriate. Catheter ablation is the most efficacious approach to eradicate PVCs but may confer increased upfront risks. Original research remains necessary to identify individuals at risk for PVC-induced cardiomyopathy and to identify preventative and therapeutic approaches targeting the root causes of PVCs to maximize effectiveness while minimizing risk.